A community of shared future for mankind: a study on the news discourse of environmental cooperation in countries along the belt and road initiative - Liu, Niwen; Yasin, Megat Al Imran; Alsagoff, Syed Agil; Ng, Chwee Fang; Li, Mengyu (Public Library of Science, 2023)
‘The Belt and Road Initiative’ (B&R) was proposed by Chinese President Xi Jinping in September and October 2013 and is now actively supported and participated by more than 100 countries and international organizations. B&R has become a hot topic all over the world since its inception. However, the environmental issues arising from this Initiative should not be underestimated. The concept of ‘A Community of Shared Future for Mankind’ is being promoted under the context of globalization, and there has been a lot of coverage in the mainstream media from various countries on the topic of environmental cooperation along B&R. This study takes a sample of reports on the ‘Belt and Road Environmental Cooperation’ from July 2021 to August 2022 and uses Van Dijk’s theory of news discourse analysis to analyze 20 articles in depth. This study attempts to explore the kind of thematic structure and lexical style that the mainstream newspapers from different countries use to report the environmental cooperation among the countries along B&R, also the implications of such a thematic structure and lexical style, and the characteristics of the discourse construction of mainstream newspapers in different countries. The research has found that B&R countries are used to holding a positive attitude to make a report and seek international cooperation. The headlines are mostly made up of nouns, and both direct and indirect quotations are used. Besides, to enhance the truth of the report, different number types are also involved; the theme structures are often made up of a two-level hierarchy.